Patterns in invoicing currency in global trade - Emine Boz; Camila Casas; Georgios Georgiadis; Gita Gopinath; Helena Le Mezo; Arnaud Mehl; Tra Nguyen (European Central Bank (ECB), 2020)
This paper presents the most comprehensive and up-to-date panel data set of invoicing currencies in global trade. It provides data on the shares of exports and imports invoiced in US dollars, euros, and other currencies for more than 100 countries since 1990. The evidence from these data confirms findings from earlier research regarding the globally dominant role of the US dollar in invoicing - despite the comparatively smaller role of the US in global trade - and the overall stability of invoicing currency patterns. But the evidence also points to several novel stylised facts. First, both the US dollar and the euro have been increasingly used for invoicing even as the share of global trade accounted for by the US and the euro area has declined. Second, the euro is used as a vehicle currency in parts of Africa, and some European countries have seen significant shifts toward euro invoicing. And third, as suggested by the dominant currency paradigm, countries invoicing more in US dollars (euros) tend to experience greater US dollar (euro) exchange rate pass-through to their import prices; also, their trade volumes are more sensitive to uctuations in these exchange rates.
Keywords: F14; F31; F44; 330; invoicing currency of trade; dominant currency paradigm; exchangerate pass-through